Grounding equipment - Knowlton, Robert A. (Texas : Gulf Publishing Company, 1993)
Identify the types of grounding equipment that should be use to make de-energized works safely
Narrator: Robert A. Knowlton
Keywords: Power (Mechanics); Industrial equipment